Behind Closed Doors: The Secret World Of Money Laundering - Arman Md; Ikhsan Nendi (Al-Makki Publisher, 2023)
Money laundering is a global issue that significantly threatens the integrity of financial systems and economies worldwide. This paper presents a theoretical description of money laundering and outlines the structured activities involved in the process. Additionally, it explores the electronic methods employed in money laundering, highlighting the various functions carried out using electronic gadgets and the internet. The author emphasizes the importance of understanding the characteristics, reasons, and negative impacts of money laundering on businesses and economies to gain a clear perspective on the issue. Money laundering is a criminal act in most countries, and economically developed nations have established strong barriers against it. However, the practice persists, and the paper examines how launderers circumvent these barriers and employ innovative, illegal methods to convert their illicit money into legitimate funds. The study found that money launderers employ various techniques to evade detection and prosecution, including layering, integration, and placement. Electronic money laundering is also a growing concern, with online platforms, digital currencies, and anonymous payment systems providing new avenues for launderers to conceal their activities. This paper provides an overview of money laundering and its detrimental effects on the global economy. It underscores the need for continued efforts by governments, financial institutions, and law enforcement agencies to combat this menace. Additionally, it highlights the importance of vigilance and developing innovative strategies to detect and prevent money laundering